Merle Lipton, Liberals, Marxists, and Nationalists. Competing interpretations of South African History: A convincing argument (Historia, 2021)
Merle Lipton is probably best known to historians as the author of Capitalism and apartheid (1985). She has in fact researched and written about a considerable range of South African issues. She co-edited two substantial volumes on policy questions : Land, labour and livelihoods in rural South Africa (1996) concludes more than two decades of work on South African agriculture, in particular small-scale black farming, while State and market in post-apartheid South Africa (1993) covers a wide range of economic policy issues.